The Pentahelix Strategy for Addressing Radicalism and Terrorism Issue in Surabaya - Prihandono Wibowo; Renitha Dwi Hapsari; Muchammad Chasif Ascha (Future Science, 2023)
Over the past few decades, Surabaya has maintained a reputation as a city with a high level of safety. The capital of East Java Province is devoid of any socio-political upheaval. During the 2000s, some major cities, including Jakarta and Bali, saw a wave of terrorism. However, it is noteworthy that the city under consideration, often called the